Risiko dan pengembalian saham dalam isu likuidasi perbankan AS - Kanna Kezia Anastasia Supit; Lavenia Priscillia Runtuwene (Manajemen Bisnis dan Keuangan Korporat, 2023)
During March 2023, the issue of bank liquidation in the US spread to the Indonesian capital market, so it tends to have an impact on stocks especially for the banking sector. This study aims to examine differences in stock returns in the context of US bank liquidation issues. The study uses the banking sector listed on the Indonesia Stock Exchange as a sample. The data used are daily stock market prices for the observation period of 17 February 2023 to 3 April 2023. This study finds that the average rate of return tends to decrease following the outbreak of the US bank liquidation issues. However, the findings also show that the banking sector does not have optimal risk-return performance during the observation period. Other findings also show that the rate of return on stocks before and after events has no significant difference with evidence that bank liquidation issues in the US only have a small impact.